2000
DOI: 10.1034/j.1399-3054.2000.100311.x
|View full text |Cite
|
Sign up to set email alerts
|

Protochlorophyllide‐independent import of two NADPH:Pchlide oxidoreductase proteins (PORA and PORB) from barley into isolated plastids

Abstract: bated for 4 days in darkness before plastid isolation, or The enzyme catalysing the reduction of protochlorophyllide (Pchlide) to chlorophyllide (Chlide), NADPH:Pchlide oxi-chloroplasts isolated from greenhouse-grown plants were incubated with -aminolevulinic acid (ALA), an early precursor in doreductase (POR; EC 1.6.99.1), is a nuclear-encoded protein that is post-translationally imported to the plastid. In barley the Chl biosynthesis resulting in elevated Pchlide contents in the plastids. Both barley pPORA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 27 publications
0
31
1
Order By: Relevance
“…For 35 S-pFd and 35 S-pSSU only two different precursor populations were found of which the faster eluting population had an elution time between fractions A and B containing the 35 SpPORA and 35 S-pPORB (Fig. 2B, fractions [20][21][22][23][24]. Western blotting using a heterologous anti-Hsp70 antiserum of tomato identified a 70-kDa band, which was most abundant in fractions 4-20 (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For 35 S-pFd and 35 S-pSSU only two different precursor populations were found of which the faster eluting population had an elution time between fractions A and B containing the 35 SpPORA and 35 S-pPORB (Fig. 2B, fractions [20][21][22][23][24]. Western blotting using a heterologous anti-Hsp70 antiserum of tomato identified a 70-kDa band, which was most abundant in fractions 4-20 (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…At this stage of development, the newborn seedlings prepare for light harvesting and the switch from heterotrophic to photoautotrohic growth. In older plants, the pathway remains active as well, but its operation is superimposed by a second pathway that requires binding of 14:3:3 proteins and Hsp70 and can explain the previously observed substrate-independent import mode of pPORA (21,22,32). The role of this pathway could be to provide a back-up system for the sequestration of free pigment in a nonhazardous form.…”
Section: Discussionmentioning
confidence: 92%
“…Whereas prePORB seems to follow a general import pathway, the import of prePORA into isolated chloroplasts or etioplasts was suggested to depend on its substrate Pchlide (14,15,17). Although these results could not be verified in vitro (23,24), in vivo data demonstrated that prePORA requires its substrate Pchlide to become imported into chloroplasts of cotyledons (12,13). The substrate dependence is lost in vivo in true leaves and therefore seems developmentally regulated (12).…”
mentioning
confidence: 97%
“…Work of Dahlin, Aronsson, and colleagues questioned the operation of the substrate-dependent import pathway (19)(20)(21). However, Kim and Apel (22) demonstrated substrate-dependent import of pPORA in vivo with Arabidopsis thaliana transformed with chimeric DNA encoding fusions of the transit sequence of pPORA or the whole pPORA precursor polypeptide and GFP.…”
mentioning
confidence: 99%